Cyanide hydratases and cyanide dihydratases: emerging tools in the biodegradation and biodetection of cyanide - Martínková, Ludmila; Veselá, Alicja Barbara; Rinágelová, Anna; Chmátal, Martin (Applied microbiology and biotechnology, 2015)
The purpose of this study is to summarize the current knowledge of the enzymes which are involved in the hydrolysis of cyanide, i.e., cyanide hydratases (CHTs; EC 4.2.1.66) and cyanide dihydratases (CynD; EC 3.5.5.1). CHTs are probably exclusively produced by filamentous fungi and widely occur in these organisms; in contrast, CynDs were only found in a few bacterial genera. CHTs differ from CynDs in their reaction products (formamide vs. formic acid and ammonia, respectively). Several CHTs were also found to transform nitriles but with lower relative activities compared to HCN. Mutants of CynDs and CHTs were constructed to study the structure-activity relationships in these enzymes or to improve their catalytic properties. The effect of the C-terminal part of the protein on the enzyme activity was determined by constructing the corresponding deletion mutants. CynDs are less active at alkaline pH than CHTs. To improve its bioremediation potential, CynD from Bacillus pumilus was engineered by directed evolution combined with site-directed mutagenesis, and its operation at pH 10 was thus enabled. Some of the enzymes have been tested for their potential to eliminate cyanide from cyanide-containing wastewaters. CynDs were also used to construct cyanide biosensors.
Keywords: houby; Environmental Pollutants; Structure-activity relationships; Mutant Proteins; látky znečišťující životní prostředí; biosenzitivní techniky; hydrolasy; dehydratasy; Protein Engineering; Bacteria; proteinové inženýrství; koncentrace vodíkových iontů; Enzyme Stability; DNA Mutational Analysis; Hydro-Lyases; stabilita enzymů; Biosensing Techniques; Cyanide hydratase; mutační analýza DNA; Cyanides; Fungi; biotransformace; Biotransformation; Hydrolases; Cyanide biosensors; vztahy mezi strukturou a aktivitou; Hydrogen-Ion Concentration; kyanidy; Cyanide dihydratase; Wastewater bioremediation; Hydrolysis; hydrolýza; mutantní proteiny; Structure-Activity Relationship; Enzyme production